A novel series of putative Brugia malayi histone demethylase inhibitors as potential anti-filarial drugs. - Tamara Kreiss; Tyler Eck; Brittany Hart; Sreedhar Tummalapalli; David Rotella; John Siekierka (Public Library of Science (PLoS), 2022)
Filariasis, caused by a family of parasitic nematodes, affects millions of individuals throughout the tropics and is a major cause of acute and chronic morbidity. Current drugs are largely used in mass drug administration programs aimed at controlling the spread of disease by killing microfilariae, larval forms of the parasite responsible for transmission from humans to humans through insect vectors with limited efficacy against adult parasites. Although these drugs are effective, in some cases there are toxic liabilities. In case of loiasis which is caused by the parasitic eyeworm Loa loa, mass drug administration is contraindicative due to severe side effects of microfilariae killing, which can be life threatening. Our screening program and medicinal chemistry efforts have led to the identification of a novel series of compounds with potent killing activity against adult filarial parasites and minimal activity against microfilariae. A structural comparison search of our compounds demonstrated a close structural similarity to a recently described histone demethylase inhibitor, GSKJ1/4 which also exhibits selective adult parasite killing. We demonstrated a modification of histone methylation in Brugia malayi parasites treated with our compounds which might indicate that the mode of drug action is at the level of histone methylation. Our results indicate that targeting B. malayi and other filarial parasite demethylases may offer a novel approach for the development of a new class of macrofilaricidal therapeutics.